Analisis Potensi Antimikroba Ekstrak Kunyit (Curcuma longa) terhadap Bakteri Patogen Usus di Desa Sobawagoli (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This study aims to analyze the antimicrobial potential of turmeric extract (Curcuma longa) against intestinal pathogenic bacteria in Sobawagoli Village, as well as to determine the utilization and perception of the community regarding the use of turmeric extract as a natural antimicrobial agent. The research method used was a case study with a descriptive qualitative approach through data collection techniques such as observation, interviews, and documentation. The results showed that most of the community in Sobawagoli Village had used turmeric as a traditional medicine to treat digestive disorders such as diarrhea, flatulence, and coughs. Turmeric is used in simple ways, such as boiling, grating, or squeezing to extract the juice. The curcumin and essential oil content in turmeric rhizomes are known to have antibacterial activity that can inhibit the growth of intestinal pathogens such as Escherichia coli and Shigella dysenteriae. The community has a positive perception of the effectiveness of turmeric as a natural medicine that is safe, easily available, and affordable. The results of this study confirm that the use of turmeric as an antimicrobial has a scientific basis as well as important local wisdom value that should be developed in traditional natural medicine.